Opioid switching from and to tapentadol extended release in cancer patients: conversion ratio with other opioids. (June 2013) - Mercadante, Sebastiano; Porzio, Giampiero; Aielli, Federica; Adile, Claudio; Verna, Lucilla; Ficorella, Corrado; Giarratano, Antonello; Casuccio, Alessandra
Abstract Objectives: The aim of this exploratory study was to assess the conversion ratios between tapentadol and other opioids in patients requiring an opioid switching. Methods: A prospective study was carried out in a convenience sample of consecutive patients admitted to an acute palliative care unit and a home care unit for a period of 1 year. Patients who were switched from/to tapentadol were selected. The initial ratio between tapentadol and other opioids, expressed as oral morphine equivalents was 1:3.3. The subsequent doses were flexible and were changed to fit the patients' needs. Pain intensity and distress score were recorded until opioid doses were stable. In all, 37 patients were examined; 24 and 13 patients were switched from and to tapentadol, respectively. Results: The most frequent sequences were tapentadol–morphine (18 patients) in one direction, and morphine–tapentadol (8 patients) in the other direction. In the sequence tapentadol–morphine and morphine–tapentadol, the mean final tapentadol–morphine ratios were 3.9:1 (SD 2.3), and 1:4.5 (SD 3.2), respectively, which did not differ significantly from the initial established conversion ratio. A minority of patients were switched from/to tapentadol to/from other opioids. Globally, the initial ratio did not change after switching took place. Conclusion: Data suggest that a conversion ratio between tapentadol and other opioids, expressed in oral morphine equivalents could be 1:3.3 in both direction, particularly in patients who are switched in conditions of equianalgesia. The limited number of patients prevents a definitive conclusion to be drawn, and data should be interpreted with caution, given the exploratory nature of the study and the question of the low number of patients should be addressed in future studies.